Ansley, T. R. Thornton (L/Sgt.); to Miss Vinnie Durk Montgomery; November 11 - Ansley, T. R. Thornton (Truman State University, 2014)
Sent from Manchester, England. Exact year unknown, but it was written on November 11th. These are extracts from the original letter.